(untitled) (Research, Society and Development, 2022)
Introduction: Type 2 Diabetes Mellitus is a disease characterized by micro and macrovascular complications, being one of the main risk factors for the development of cardiovascular diseases. In this sense, SGLT2 inhibitors appear, drugs with potential glycemic-lowering effects, as well as influencing other aspects that directly interfere with diabetes. Thus, this review aims to elucidate the risk-benefit of the use of these drugs as well as the comparison between them regarding the advantages offered. Methodology: the present study consists of an exploratory integrative literature review. A bibliographic survey was carried out through electronic searches in the following databases: Virtual Health Library (BVS), Scientif Electronic Library Online (SciELO) and National Library of Medicine (PubMed). Results and Discussion: Several studies have shown the cardioprotective effects of SGLT2 inhibitors in patients with DM2. These studies showed that Empaglifozin, Canagliflozin and Dapaglifozin considerably reduce blood glucose and have better effects than hypoglycemic agents that use exogenous insulin or that induce endogenous insulin. In addition, they are related to decreased blood pressure, improved arterial compliance, reduced visceral adiposity, reduced serum uric acid levels and oxidative stress, as well as improved body weight. However, they also have adverse effects, especially urinary tract infection. Conclusion: despite the great effectiveness, more studies are needed, including the Brazilian population, for further elucidation about these drugs and their use as therapy by the Health System.